LAYANAN BIMBINGAN KELOMPOK TENTANG SOPAN SANTUN SISWA KELAS VIII DI SMP NEGERI 21 PONTIANAK - Nilasari, Nilasari; Astuti, Indri; Yusuf, Abas (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractGood manners, respect, smiles, and obedience to a rule. The correct attitude of manners is to bring out the good personal and respect for everyone. From speech, people can see our modesty. Good/bad, for example again in a crowded situation where we will pass the path, if we are sure we will say the word excuse us for the person we are going to pass. Method used is a descriptive method and the form of research is a form of poll. Sample in this study as much as 38 SMP Negeri 21 Pontianak students. This research uses a quantitative approach. The data collection techniques used are indirect communication techniques and data gathering tools with Angket. While the data analysis technique uses the percentage formula. Based on the results of this study shows that the group guidance service on class VIII courtesy of SMP Negeri 21 Pontianak is the first, second, third, and fourth phase with the category